Characterization of Indigenous Goats Type using Morphological Characters and Body Measurements in Sinana district, Bale zone, South East Ethiopia (Global Journal of Science Frontier Research, 2016)
The study was conducted on Characterization of Indigenous Goats Type Using Morphological Characters and Body Measurements in Sinana district, Bale zone, South East Ethiopia, with objectives of on-farm characterization of Indigenous Goats type using linear body measurement and qualitative physical characteristics and investigating the prediction of live weight using body measurement for Indigenous Goats type. For this study, purposive sampling and simple random sampling methods were used for selection of kebeles and experimental goats, respectively. About 120 animals were sampled for body measurements and qualitative characters. Statistical analysis system software was applied for analyzing of data. Goats type in the study area were characterized as red dominant coat color (35.83%), concave head profile (37.5%), no wattle (100%), have no toggles (86.67%), have no ruff (75%),horned (100%) of about (75%) were straight horn shape.
Keywords: body measurements; morphological charact- erization; indigenous goats type; sinana district